INVENTION OF POLITICS: BETWEEN AGONISTIC RHETORIC AND POLEMICAL DIALECTIC - Trachuk, Mykyta (The Journal of V. N. Karazin Kharkiv National University, Series Philosophy. Philosophical Peripeteias, 2024)
The article presents an attempt at a philosophical analysis of the rhetorical origins of politics in an inseparable relationship with the political value of rhetoric. The author examines some contemporary projects of “reinventing politics” (especially in the actual Ukrainian context), describing them as phenomena of the overreflection of modernity, or secondary reflection of modernity. After postmodern criticism, the development of communication theory, and the complexive theoretical constructions of theorists of the Second (“reflexive”) Modern, contemporary political philosophy, apparently, has not been able to recover from the modern catastrophes of the XXth century, because contemporary theorists of new/other modern(s) continue to follow the same beaten paths of modernist philosophizing, where various reconstructions and “reinventions” are worth much more than the actual value of invention. Starting from the visualized opposition of agonistic and polemical culture, the author offers his own project of thinking about politics as a rhetorical invention, that’s open to endless creative modifications, in its opposition to polemics (as a belligerent dispute), which is seen as an apolitical and antagonistic phenomenon to politics. The political state of society, where the city-fortress and the city-community intersect, is considered as a kind of special political topos as a place where enlightened consciousness is concentrated, in its dialectical relationship with the belligerent anxiety of polemos (as with the sacred unconscious, pushed to the margins in the course of enlightenment secularization). Drawing on Aristotle's ideas, the author develops a critique of war as a phenomenon opposed to the principles of endless political invention, which should be based on developed popular eloquence. The phenomenon of fascization of European societies in the twentieth century is interpreted as an attempt to destroy politics through the politicization of polemics. In order to protect against such relapses of the apolitical, the author proposes to develop a new political theory in which democratic politics would be closely linked to rhetoric and reinvent itself in it, developing the traditions of popular eloquence (as an opportunity for everyone to speak in their own voice). It is proposed to think of political rhetoric as an art of multiple variations, while dialectic (as an art that pits clear binary polemical oppositions of being-non-being and good-evil against each other) should finally leave politics alone. In opposition to politics as a rhetorical invention, polemos appears as a manifestation of apolitical dialectic, and therefore the study of the phenomenon of war requires going far beyond politics to the non-political realm, where mostly religious issues matter, not political ones.